2003
DOI: 10.1590/s0004-27302003000400013
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos neuroendócrinos da síndrome metabólica

Abstract: Arq Bras Endocrinol Metab vol 47 nº 4 Agosto 2003 410 RESUMOA síndrome metabólica (SM) é caracterizada por alterações no metabolismo glicídico, obesidade, hipertensão e dislipidemia. Estas alterações metabólicas interrelacionam-se com diversos eixos endócrinos controlados pelo hipotálamo e pela hipófise. A obesidade central parece relacionar-se a uma hiperativação do eixo hipotálamo-hipófise-adrenal, como também do sistema nervoso simpático, que poderia levar a um quadro de hipercortisolismo sub-clínico e hipe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0
12

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 96 publications
1
14
0
12
Order By: Relevance
“…The reasons for the association between metabolic syndrome and hypogonadism are not completely clear. It has been suggested that insulin resistance, acting through signs mediated by the adipose tissue, including increased levels of leptin, would have a direct role in the regulation of gonadal function, thus decreasing the concentrations of testosterone (1,4,25,26). At the same time, pro-inflammatory cytokines, such as TNF alpha, IL-1 and IL-6, produced by visceral adipocytes, are also associated with insulin resistance (27,28).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The reasons for the association between metabolic syndrome and hypogonadism are not completely clear. It has been suggested that insulin resistance, acting through signs mediated by the adipose tissue, including increased levels of leptin, would have a direct role in the regulation of gonadal function, thus decreasing the concentrations of testosterone (1,4,25,26). At the same time, pro-inflammatory cytokines, such as TNF alpha, IL-1 and IL-6, produced by visceral adipocytes, are also associated with insulin resistance (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…This would inhibit gonadotrophin production centrally, and further decrease testosterone levels. Subsequently, the decrease in testosterone would facilitate a higher deposition of body fat and a more severe degree of hypogonadism (1,7,44).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations